Estabilidad cromática de 4 resinas compuestas sometidas a diferentes sustancias pigmentantes, Iquitos, 2024 - Cáceres Tong, Sixto Alfredo (2024)
OBJECTIVE: The study aimed to determine the chromatic stability of 4 composite resins subjected to different pigmenting substances, Iquitos, 2024. METHOD: From a methodological perspective, the research is classified as quantitative, with an explanatory level of a correlational descriptive type, using a non-experimental design. For the investigation, 40 composite resin samples were selected. RESULTS: The results showed that Filtek Z350 XT resin maintained notable chromatic stability only when immersed in distilled water; However, its color was altered when exposed to pigments such as coffee, chicha morada, turmeric and paprika. For its part, the Forma resin managed to retain its original color in distilled water, but showed notable chromatic instability throughout the three evaluation periods. The Tetric N-ceram resin also lost its original color, its chromatic stability being significantly affected by the pigmenting substances. Finally, the Llis resin did not maintain its original color; However, it demonstrated notable chromatic stability when immersed in distilled water during all the periods evaluated.